2009
DOI: 10.1021/ja905432x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Tetraarylborates as Effective Nucleophiles in Rhodium/Diene-Catalyzed 1,4-Addition to β,β-Disubstituted α,β-Unsaturated Ketones: Catalytic Asymmetric Construction of Quaternary Carbon Stereocenters

Abstract: A rhodium-catalyzed 1,4-addition of sodium tetraarylborates to beta,beta-disubstituted alpha,beta-unsaturated ketones is described. Highly efficient asymmetric catalysis has also been achieved by employing a readily available chiral diene ligand, leading to the construction of quaternary carbon stereocenters with high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(77 citation statements)
references
References 50 publications
2
72
1
2
Order By: Relevance
“…From mechanistic aspects, it is clear that the reaction proceeds through the formation of an rhodium/aryl species, and the enone is activated by the Lewis acidity of the aluminum reagent. [6,12] In summary, we have shown that aryl alanes are excellent nucleophiles for the rhodium-catalyzed conjugate addition reaction. Whilst elevated temperatures are usually required with boron nucleophiles, only 1.2 to 1.5 equivalents of alane afforded the same transformation overnight at 5 8C.…”
Section: L3mentioning
confidence: 96%
See 1 more Smart Citation
“…From mechanistic aspects, it is clear that the reaction proceeds through the formation of an rhodium/aryl species, and the enone is activated by the Lewis acidity of the aluminum reagent. [6,12] In summary, we have shown that aryl alanes are excellent nucleophiles for the rhodium-catalyzed conjugate addition reaction. Whilst elevated temperatures are usually required with boron nucleophiles, only 1.2 to 1.5 equivalents of alane afforded the same transformation overnight at 5 8C.…”
Section: L3mentioning
confidence: 96%
“…[5] Only recently have a few articles appeared that report the rhodium-catalyzed formation of quaternary centers on enones, [6] of which one [6b] presents a single example with poor yield. In the more general studies, [6a,c] several parameters in the original protocol [7] needed to be changed: [7] boronic acids were replaced by tetraarylborates [6a] and boroxines, [6c] and chiral diene ligands were used because commercially available binap did not give any conversion.…”
mentioning
confidence: 99%
“…Quaternary stereocenters can be constructed at the b-position of carbonyl groups by catalytic asymmetric conjugate addition of carbon-based nucleophiles to b,b-disubstituted a,b-unsaturated carbonyl compounds [61][62][63][64]. We previously developed a catalytic enantioselective conjugate addition of cyanide to b-monosubstituted a,b-unsaturated N-acylpyrroles and ketones using gadolinium catalysts derived from ligands 5 and 7 [65][66][67][68][69][70][71].…”
Section: Catalytic Enantioselective Conjugate Addition Of Cyanide To mentioning
confidence: 99%
“…Sogar quartäre Zentren lassen sich mit gutem ee-Wert, wenn auch deutlich geringerer Ausbeute aufbauen (Eintrag 11). [18] Von besonderem Interesse ist die Koordinationsweise dieser neuen Ligandenklasse. [16] Tabelle 1: Eignung der Olefin-Oxazolin-Liganden 1-18 für die 1,4-Addition von Phenylboronsäure an Cyclohexenon.…”
Section: Björn T Hahn Friederike Tewes Roland Fröhlich Und Frank Gunclassified